(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2024)
The global arena of international relations is placing increasing importance on the subject of climate change. The disruptions in natural weather patterns are giving rise to a wide array of challenges in ecological, sociopolitical, and economic systems. This piece of writing investigates the concept of marginalization brought about by the effects of climate change. The analysis adopts a multi-faceted approach, utilizing the framework of climate justice. The primary focus lies in understanding how climate-induced marginalization impacts a nation’s social structure, especially affecting disadvantaged communities. Following that, the conversation delves into making a comparison among different countries, examining their contributions to climate change and the subsequent difficulties they encounter. The article also underscores the insufficiencies in international frameworks aimed at mitigating climate change, underscoring the lack of accountability during their development. Additionally, the problem of climate-induced marginalization is evaluated in the context of the Sustainable Development Goals, and suggestions are put forth to effectively tackle this issue.